PENERAPAN ASAS SEDERHANA, CEPAT DAN BIAYA RINGAN DALAM PENYELESAIAN PERKARA MELALUI PENGADILAN ELEKTRONIK DAN PENGADILAN BIASA DI PENGADILAN AGAMA PONTIANAK - IDSA LU’LU’ FATHINA FARHANI NIM. A1011191262 (Jurnal Fatwa Hukum, 2023)
AbstractThe judiciary in Indonesia adheres to one of the principles, namely the principle of simple, fast, and low-cost trials as stipulated in Law Number 48 of 2009. Currently, the Supreme Court has developed an e-Court system to support electronic courts. In carrying out judicial processes in electronic courts and ordinary courts, of course, some differences are realized or not realized by the litigants, especially in the application of the principle of simple, fast, and low cost. The formulation of the writing problem is how to apply the principle of simple, fast, and low cost in resolving cases through electronic courts and ordinary courts at the Pontianak Religious Court. The research aims to obtain data and information related to the application of simple, fast, and low-cost principles in resolving cases through electronic courts and ordinary courts at the Pontianak Religious Court. revealed the advantages and disadvantages in realizing the principle of simple, fast and low cost at the Pontianak Religious Court, and found the efforts of the Pontianak Religious Court in overcoming deficiencies in the implementation of case settlements through electronic courts and ordinary courts. That the application of the simple, fast, and low-cost principle at the Pontianak Religious Court has been very well implemented. However, there are differences in the implementation in the field, especially in terms of fast and low cost. The advantages of electronic courts are that the case settlement process is relatively fast and the drawback is that it is prone to errors in the e-Court system. The Pontianak Religious Court's efforts to overcome these deficiencies include: Providing facilities and infrastructure to support the use of e-Court and improving services, appointing e-Court corner officers, continuing to make efforts to upgrade related systems and services for the smooth running of litigation at the Pontianak Religious Court.Keywords: The principle of simple, fast and low cost, electronic courts, ordinary courtsAbstrak Peradilan di Indonesia menganut salah satu asas yaitu Asas Peradilan Sederhana, cepat dan biaya ringan sebagaimana telah diatur dalam Undang-Undang Nomor 48 Tahun 2009. Saat ini Mahkamah Agung telah mengembangkan system e-Court guna menunjang Pengadilan elektronik. Dalam melakukan proses peradilan secara pengadilan elektronik dan pengadilan biasa tentunya ditemukan perbedaan yang disadari atau tidak disadari oleh para pihak yang beperkara, khususnya dalam penerapan asas sederhana, cepat dan biaya ringan. Rumusan masalah penulisan ini Bagaimana penerapan asas sederhana, cepat dan biaya ringan dalam penyelesaian perkara melalui pengadilan elektronik dan pengadilan biasa di Pengadilan Agama Pontianak?. Penelitian bertujuan mendapatkan data dan informasi terkait penerapan asas sederhana, cepat dan biaya ringan dalam penyelesaian perkara melalui Pengadilan elektronik dan pengadilan biasa di Pengadilan Agama Pontianak. mengungkapkan kelebihan dan kekurangan dalam mewujudkan asas sederhana, cepat dan biaya ringan di Pengadilan Agama Pontianak, menemukan upaya Pengadilan Agama Pontianak dalam mengatasi kekurangan dalam pelaksanaan penyelesaian perkara melalui pengadilan elektronik maupun pengadilan biasa. Bahwa penerapan asas sederhana, cepat dan biaya ringan di Pengadilan Agama Pontianak telah diterapkan dengan sangat baik. Namun terdapat perbedaan dalam pelaksanaannya di lapangan, khususnya dalam asas cepat dan biaya ringan. Kelebihan dalam pengadilan elektronik yakni proses penyelesaian perkara terhitung cepat dan kekurangannya, rawan terjadi error pada sistem e-Court. Upaya pengadilan Agama Pontianak dalam mengatasi kekurang tersebut antara lain: Menyediakan sarana dan prasarana untuk medukung pemanfaatan e-Court dan meningkatkan pelayanan, menunjuk petugas pojok e-Court, terus berupaya melakukan upgrading terkait sistem dan pelayanan demi lancarnya proses berperkara di Pengadilan Agama Pontianak.Kata Kunci : Asas sederhana, cepat dan biaya ringan, pengadilan elektronik, pengadilan biasa